Creative cities and the concept of diversity - Jan Wedemeier (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2009)
This paper presents a review on theories and empirical studies relevant for the concept of diversity of people in the creative cities literature. The upcoming question enquires which role diversity plays in creative cities. The paper aims to summarize and compare key diversity components considered in research. Based on the review, conclusions are drawn to the attention of policy makers that soft location factors, such as the diversity of people, matter for urban development.
Keywords: 330; creative cities; diversity of people; urban growth